1997
DOI: 10.1002/(sici)1096-9888(199704)32:4<425::aid-jms493>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Microdialysis Procedure for Electrospray Ionization Mass Spectrometry of Biological Samples

Abstract: Significant advances in the area of microdialysis which allowed more effective handling of small volumes (microliters) of samples, more efficient desalting and enhanced mass spectrometric detection sensitivity are described. The previously reported on‐line coupling of microdialysis with electrospray ionization (ESI) mass spectrometry has been found to be highly effective; however, direct coupling requires relatively high sample flow rates (∽2 μl min‐1) to obtain a stable ESI current compared with the flow rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 8 publications
1
43
0
Order By: Relevance
“…Moreover, improved desalting can also be a consequence of higher temperature of the electrosprayed column effluent. This hypothesis is supported by experiments of Liu et al [37] and Walters et al [38], who reported an increased desalting performance by heating nucleic acids solutions prior to ESI-MS.…”
Section: -4mentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, improved desalting can also be a consequence of higher temperature of the electrosprayed column effluent. This hypothesis is supported by experiments of Liu et al [37] and Walters et al [38], who reported an increased desalting performance by heating nucleic acids solutions prior to ESI-MS.…”
Section: -4mentioning
confidence: 57%
“…In a report by Liu et al [37], the salt tolerances of multiple buffer exchange, organic base addition, and microdialysis were studied by adding high concentrations of sodium chloride to the analyzed nucleic acid solutions. This group reported that microdialysis offered the highest desalting performance among the three techniques, which enabled the mass spectrometric detection of nucleic acids from solutions containing 0.5 mol/l sodium chloride.…”
Section: Characterization Of Salt Tolerance Of Icemsmentioning
confidence: 99%
“…So far, the most successful clean-up procedures rely on ethanol precipitation or use of spin columns followed by microdialysis as a final desalting step (16,21,30,31,34,(38)(39)(40)(41)(42)(43)(44). However, these procedures are time-and labor-intensive and incur significant sample loss.…”
Section: Purification Of Pcr Productsmentioning
confidence: 99%
“…In the past, several strategies were developed to obtain sufficiently pure DNA samples. Most involved either ethanol precipitation (16,21,22,33,(38)(39)(40)(41) or centrifugation through appropriate filter systems/spin columns (30)(31)(32)34,41) followed by microdialysis (42)(43)(44) or incubation with cation exchange particles (17) for final desalting.…”
Section: Introductionmentioning
confidence: 99%
“…PCR products were ethanol precipitated [6,7] and microdialyzed [8] prior to ESI-FTICR-MS [9]. Mass spectra were acquired in the negative-ion mode using a modified ESI-FTICR mass spectrometer (IonSpec Inc., Irvine, CA) with a 9.4 tesla superconducting magnet (Cryomagnetics, Oak Ridge, TN).…”
Section: Methodsmentioning
confidence: 99%